Forest Bioeconomy and Climate Change - Hetemäki, Lauri; Kangas, Jyrki; Peltola, Heli (Managing Forest Ecosystems, 2022)
This edited open access volume explores the role of forest bioeconomy in addressing climate change. The authors put a particular focus on planetary boundaries and how the linear, growth-oriented economy, is coupled with climate change and environmental degradation. Biobased products and sustainable production paths have been developed, but how can they be scaled in order to lead to an economic paradigm shift? This and other questions are discussed throughout the volume. Since science indicates that climate change will continue this century, the authors also analyse how forests can be adapted to increasing forest disturbances that changing climate are expected to cause. The authors propose climate-smart forestry as useful approach for climate mitigation and adaptation of forests to climate change, as wells as sustainable increase of economic well-being based on forestry. The book illustrates the application of climate-smart forestry in the Czech Republic, Finland, Germany and Spain, i.e., in EU countries with quite different forests and forest sectors. This proactive and inspiring volume is an essential resource for Forest Management professionals, decision makers, scientists, and forestry students. ;